ANALISIS PENGARUH GROWTH MINDSET TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII UPT SMP NEGERI 1 LINGGO SARI BAGANTI - Okviani Syafti; Sefrinal Sefrinal; Yanti Nazmai Ekaputri; Nesa Arzi Putri; Devina Shafira Maharani (Jurnal Manajemen Pendidikan, 2026)
This study aims to determine the effect of growth mindset on the mathematical problem-solving ability of seventh-grade students at UPT SMP Negeri 1 Linggo Sari Baganti. This type of research is quantitative research with simple linear regression test analysis to determine the effect of growth mindset on mathematical problem-solving ability. Data collection techniques are using questionnaires to determine students' growth mindset data and tests to determine students' mathematical problem-solving ability, with a research sample of 26 students of grade VII.4. Based on the results of the analysis, students' growth mindset scores were obtained with the highest score of 76, the lowest score of 61, and an average of 68.42 which is in the medium category. The results of the students' mathematical problem-solving ability test showed the highest score of 98, the lowest score of 22, and an average of 76.46 which is in the medium to high category. The results of the study indicate that growth mindset has a positive effect on students' mathematical problem-solving ability, meaning that the higher a student's growth mindset, the more likely it is that the mathematical problem-solving ability also increases.